Plumbing layout of basement storey of BRAC University New Campus - BUCG-ABC Joint Venture (BUCG-ABC JV) (BRAC University, 2024)
This record contains plumbing as-built drawings of the Brac University New Campus Project. It consists of pdf versions of drawings.